Impact of street geometry on downward longwave radiation and air temperature in an urban environment - Simone Blankenstein; Wilhelm Kuttler (Meteorologische Zeitschrift, 2004)
A study on urban geometry has been carried out with regard to urban climate in a medium-sized central European city. Thereby the interrelation between the sky view factor (SVF, the portion of visible sky seen by an observer), downward longwave radiation and air temperature was analysed to get a closer look to the interaction of horizon obstructions, thermal radiation from urban surfaces and the urban heat island. Downward longwave flux and air temperature were measured by car traverses through the city of Krefeld, Germany, during clear and calm summer nights in 2003. The traverse included sections with buildings as well as sections with vegetation. Correlation of longwave radiation and SVF was close and negative with a coefficient of determination R2 = 0.91, but urban heat island intensities (UHI, calculated from air temperature differences) along the route were weakly correlated with the SVF (0.07≤ R2≤ 0.39). With buildings, UHI increased with a reduced SVF, but no tendency was found below trees. This was probably a main result from local topographic effects (cold air accumulation). The study indicates that a nocturnal urban heat island on a microscale is not only affected by horizon obstructions, but also by the spatially variable thermal properties of materials. Moreover, advection diminishes site specific air temperature differences even during low winds. On the other hand, longwave radiation strongly depends on geometric factors and can be predicted well with the SVF.